A study of students' perceptions of the compulsory AFIS course at IIUM - Daud, Nadwa; Chik, Abdul Rahman (IIUM Press, 2009)
Arabic for Islamic Studies (AFIS)is a compulsory course offered by the Department of Arabic Language & Literature (DALL) at the International Islamic University Malaysia (IIUM) to undergraduate students majoring in Islamic Revealed Knowledge & Heritage (IRKH) with different specializations (Fiqh and Usul Fiqh, Usuluddin and Dakwah, and Qur'an and Sunnah). It falls under the umbrella of ASP. ASP needs analysis is the first step to design a language course, which accommodates learners' needs. The study will attempt to investigate these students' Arabic language needs. Although this particular ASP course for IRKH programme at IIUM has been in existence for many years,it is not based on a systematic needs analysis; neither has it been subjected to evaluation since its inception. However, the strong emphasis placed by IIUM on constant improvement of the quality of research and teaching has made it imperative taht a proper needs analysis be carried out. As a result, the researchers carried out an investigation into the needs of the students of the IRKH programme at IIUM. A quantitative-cum-qualitative research methodology was adopted, with questionnaires, interviews and researchers' observations being the main data-gathering tools. In order to ensure that the information regarding the needs of the students was identified in an in-depth and comprehensive manner, attempts were made to include, in addition to the IRKH students, ASP practitioners at IIUM, content lecturers and administrators. The needs and wants of the students were identified and recommendations were made as guidelines for designing an ASP course for IRKH programme at IIUM.